Motivational factors for the practice of futsal and football by children and adolescents: a systematic review - Coelho, Eduardo (2022)
Understanding the factors that motivate children and adolescents to practice sports helps in the training’s development to improve adherence, the teaching and the learning process. This study is a systematic review whose objective was to identify the main motivational factors for the practice of futsal and football by children and adolescents. The searches were performed in the SciELO, BVS, Scopus and DOAJ databases, in addition to the Revista Brasileira de Futsal and Futebol and Revista Brasileira de Futebol. The Portuguese Articles that were included verified the motivation of children and/or adolescents to practice football or futsal. Data were extracted from the articles regarding the identification of the article, characterization of the participants, context of insertion in the modality, characterization of exposure to the modality, instrument used to measure motivation and results. A total of 149 articles were found in the search and 14 of them were included in the review. 14 studies provided data on 897 children and adolescents involved in futsal and football’s practice in school physical education, schools, social projects and team sports and clubs. The age of the participants ranged between 7 and 18 years. Children and teenagers who practice football and futsal are motivated to practice these sports predominantly due to the health factor. Adolescents who practice football showed higher levels of intrinsic motivation than extrinsic. In school physical education, sports competence was the least important motivational factor. In schools and projects, the factors sporting competence and physical fitness also stood out as important.